Some Historical Connections between Bangladesh and Indonesia - Muhammad Abdul Karim (Sunan Kalijaga: International Journal of Islamic Civilization, 2018)
Indonesia and Bangladesh are two countries with Muslim majority. The relationship between the two countries is getting closer that can be seen from the cooperation built by the two states. The two states have a long historical relationship because they have some similarities, for example, they have the same culture, the same writing, and the same language. They have intensive contact in trade. This paper explains the historical relationship of Indonesia and Bangladesh that has been built for a long time. This paper finds that the relationship getting closer and closer between Indonesia and Bangladesh nowadays is the continuity of the long historical relationship; it is not the new one for the two countries.